(3GdeMGSHI GdOhdjI heYGjjQgG (B/s - (3GdbGVj, MSjfs; (3MeOGf, eGehf s ((3YeGf(B: s (3OGQ GdKbGaI(B, s, 2008)
(3jgOa gPG GdcJGH Gdi JbOje EWGQ fXQj hYedj dOQGSI GdeMGSHI GdOhdjI ef MjK fThFgG hJWhQgG hYdGbGJgG eY YOI eaGgje eKd GdYehdI hKhQI GdeYdheGJ hGdJLGQI GdEdcJQhfjI Je JcQjS GdHGH GdChd dYQV GdeONd Gdi GdeMGSHI GdOhdjI hGdPj jVe KdGKI aUhd hjgJe GdHGH GdKGfj HYQV JWHjbGJ eYGjjQ GdeMGSHI GdOhdjI MjK JfGhd eMGSHI GdCUhd habkG deYGjjQ GdeMGSHI GdOhdjI hQcR ajg Ydi ehVhYGJ gGeI eKd eMGSHI GdGSJgdGc heMGSHI YbhO GdEfTGA ceG JVef eMGSHI GdJVNe hYQV eTcdI EYOGO GdbhGFe GdMGdjI habG ddeYGjjQ GdeMGSHI GdOhdjI CeG GdHGH GdKGdK abO cGf deYGjjQ GdJObjb GdOhdjI YQV ajg CgejI GdJObjb hCgOGa GdeYGjjQ GdTNUjI s
(3HjHdjhZQGajG U(B.317s
Keywords: (3GdeMGSHIs; (3GdeMGSHI GdOhdjIs; (3eYGjjQ GdeMGSHIs